2010
DOI: 10.1039/c000782j
|View full text |Cite
|
Sign up to set email alerts
|

Pore-lattice deformations in ordered mesoporous matrices: experimental studies and theoretical analysis

Abstract: The sorption of fluids in mesoporous silica is an important physical phenomenon with a wide range of applications. Traditionally, mesoporous materials have been considered as inert scaffolds for the sorption and condensation reaction of the fluid. Here we present in situ small angle X-ray diffraction experiments providing evidence for a sorption strain induced in the solid that manifests itself as a change in the lattice parameter of the ordered mesopore array as the pores gradually adsorb fluid material. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 39 publications
8
59
0
Order By: Relevance
“…Typical lattice parameters, pore sizes, as well as the pore volume fractions of these materials are listed in Table 2.1 of Ref. 21. For the sake of concreteness we focus only on experiments using pentane as the adsorbate.…”
Section: Experimental Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Typical lattice parameters, pore sizes, as well as the pore volume fractions of these materials are listed in Table 2.1 of Ref. 21. For the sake of concreteness we focus only on experiments using pentane as the adsorbate.…”
Section: Experimental Backgroundmentioning
confidence: 99%
“…To make contact with a specific experimental situation we focus on sorption experiments [21] employing ordered mesoporous silica of the type MCM-41 [14]. These materials consist of grains of roughly 1 µm size, containing cylindrical nanopores on a well ordered twodimensional hexagonal pore lattice with pore diameter of the order of 3-4 nm and narrow size distributions.…”
Section: Experimental Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of papers employed molecular modeling techniques for predictions of adsorption-induced strains in various nanoporous materials: Monte Carlo simulations 40,[81][82][83][84][85][86][87][88][89][90][91][92] or classical density functional theory (DFT). [93][94][95][96] At the same time, several purely analytical theories were also proposed.…”
Section: B Quantitative Thermodynamic Theoriesmentioning
confidence: 99%
“…81 In addition to qualitatively reproducing the observed adsorption-induced deformation, they showed that network flexibility significantly alters the adsorption and desorption isotherms as compared to a rigid network. Schoen and coworkers 83,84 performed a Monte Carlo simulation study for a model system, Lennard-Jones (LJ) fluid adsorption in a slit pore, where the solid atoms were allowed to elastically depart from their equilibrium sites, by a harmonic potential. Such a system is able to be strained normal to the pore walls, changing the width of the slit pore.…”
Section: Coupling Between Thermodynamic and Elastic Aspects Of Adsmentioning
confidence: 99%